2021
DOI: 10.3390/app11167322
|View full text |Cite
|
Sign up to set email alerts
|

SOPRENE: Assessment of the Spanish Armada’s Predictive Maintenance Tool for Naval Assets

Abstract: Predictive maintenance has lately proved to be a useful tool for optimizing costs, performance and systems availability. Furthermore, the greater and more complex the system, the higher the benefit but also the less applied: Architectural, computational and complexity limitations have historically ballasted the adoption of predictive maintenance on the biggest systems. This has been especially true in military systems where the security and criticality of the operations do not accept uncertainty. This paper de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In the arena of machine learning (ML) and especially fault detection systems, quite a few works can be found in the literature. Studies alike employ several prediction techniques, including regularized linear regression methods such as L1 (lasso) and L2 (ridge), or long short-term memory (LSTM)-based networks [ 34 ]. In this context, previous research has used artificial neuronal networks (ANN) [ 35 ] and decision trees [ 36 ], as well as support vector machines (SVM) [ 37 , 38 ] or the k-nearest neighbor technique (k-NN) as one of the most common for fault classification [ 39 ].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In the arena of machine learning (ML) and especially fault detection systems, quite a few works can be found in the literature. Studies alike employ several prediction techniques, including regularized linear regression methods such as L1 (lasso) and L2 (ridge), or long short-term memory (LSTM)-based networks [ 34 ]. In this context, previous research has used artificial neuronal networks (ANN) [ 35 ] and decision trees [ 36 ], as well as support vector machines (SVM) [ 37 , 38 ] or the k-nearest neighbor technique (k-NN) as one of the most common for fault classification [ 39 ].…”
Section: Related Workmentioning
confidence: 99%
“…These logistics applications are difficult systems that require in-depth knowledge and expert analysis. Likewise, some authors have reviewed these tools proposing an alternative semi-unsupervised predictive maintenance system [ 34 ]. From our side, we focus on a novel fault detection system approach based on operational data provided by the ATAVIA application, as discussed below.…”
Section: Case Of Studymentioning
confidence: 99%
“…Examples of this case are found on the one hand in industrial processes (Bampoula et al, 2021; Bekar et al, 2020; Chang et al, 2021; Kim et al, 2021; Kolokas et al, 2020; Lepenioti et al, 2020; Li et al, 2017; Morariu et al, 2020; Rafique et al, 2018; Ruiz‐Sarmiento et al, 2020; Susto et al, 2015; Uhlmann et al, 2018; Zschech et al, 2019), in production lines (Ayvaz & Alpay, 2021; Azab et al, 2021; Cerquitelli et al, 2021; Fathi et al, 2021; Giordano et al, 2021; Liu et al, 2021), in power plants (de Carvalho Chrysostomo et al, 2020; Khodabakhsh et al, 2018; Sun et al, 2021; Zhang, Liu, et al, 2018), in wind turbines (Chen, Hsu, et al, 2021; Leahy et al, 2018; Santolamazza et al, 2021), in ventilation systems (Fernandes et al, 2020), cryogenic pumps (Crespo Márquez et al, 2020), heat meters (Pałasz & Przysowa, 2019), press machines (Serradilla et al, 2021), or water treatment plants (Srivastava et al, 2018). Another common scenario for PdM is related to transportation: different types of land vehicles (Chen et al, 2020; Patil et al, 2021; Prytz et al, 2015; Shafi et al, 2018), aircrafts (Baptista et al, 2021; Basora et al, 2021; Ning et al, 2021; Savitha et al, 2020; Yang et al, 2017), and naval ships (Berghout et al, 2021; Fernández‐Barrero et al, 2021; Gribbestad et al, 2021) have been monitored through their electronic control units. Also, Ribeiro et al (2016) found a case that monitors train doors status.…”
Section: Data Mining In Predictive Maintenancementioning
confidence: 99%
“…After the phase of novelty detection, other ML methods based on unsupervised learning are employed to explain the characteristics of the anomalies detected. Other approach of AE designed to deal with time series by means of LSTM in its internal layers is explored in several works (Bouabdallaoui et al, 2021; Fernández‐Barrero et al, 2021; Ning et al, 2021). The anomalies are detected from the differences between time series at the input and at the output.…”
Section: Data Mining In Predictive Maintenancementioning
confidence: 99%
See 1 more Smart Citation